2014
DOI: 10.1128/mcb.00814-14
|View full text |Cite
|
Sign up to set email alerts
|

Plk1 Phosphorylation of PTEN Causes a Tumor-Promoting Metabolic State

Abstract: f One outcome of activation of the phosphatidylinositol 3-kinase (PI3K) pathway is increased aerobic glycolysis, but the upstream signaling events that regulate the PI3K pathway, and thus the Warburg effect, are elusive. Increasing evidence suggests that Plk1, a cell cycle regulator, is also involved in cellular events in addition to mitosis. To test whether Plk1 contributes to activation of the PI3K pathway, and thus aerobic glycolysis, we examined potential targets of Plk1 and identified PTEN as a Plk1 subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 44 publications
8
68
0
Order By: Relevance
“…We have also shown that Plk1 phosphorylation of Hbo1 and Orc2, two members of the DNA replication machinery, regulates DNA synthesis by affecting chromatin loading of prereplicative complexes (16,44). More recently, we discovered that Plk1 phosphorylation of PTEN leads to a tumor-promoting metabolic state with increased glycolysis and glutamine anaplerosis, two hallmarks of cancer cells (40). Of interest, others reported previously that Plk1 interacts with and phosphorylates axin and that Plk1 phosphorylation of axin is involved in proper centrosome formation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have also shown that Plk1 phosphorylation of Hbo1 and Orc2, two members of the DNA replication machinery, regulates DNA synthesis by affecting chromatin loading of prereplicative complexes (16,44). More recently, we discovered that Plk1 phosphorylation of PTEN leads to a tumor-promoting metabolic state with increased glycolysis and glutamine anaplerosis, two hallmarks of cancer cells (40). Of interest, others reported previously that Plk1 interacts with and phosphorylates axin and that Plk1 phosphorylation of axin is involved in proper centrosome formation.…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, Plk1 phosphorylation of the PTEN tumor suppressor causes its inactivation and, thus, activation of the phosphatidylinositol 3-kinase (PI3K)-AKT-mTOR pathway, a major driving force for PCa progression (40). Fifth, castration-induced elevations of Plk1 levels contribute to the constitutive activation of AR signaling, another major force in CRPC disease.…”
Section: Discussionmentioning
confidence: 99%
“…12 For example, it was recently reported that Plk1 phosphorylation of PTEN leads to its inactivation, activation of PI3K/AKT/ mTOR pathway, metabolic switch from mitochondrial respiration to glycolysis. 13 Herein, we report that Plk1 is a critical downstream target of activated NF-kB caused by low-dose arsenic and that Plk1-dependent activation of the PI3K/AKT/ mTOR pathway contributes to the metabolic switch from oxidative phosphorylation to aerobic glycolysis.…”
Section: Introductionmentioning
confidence: 94%
“…Considering that Plk1 phosphorylation of HSP70 contributes to attenuation of high-dose arsenic trioxide (5 mM for 24 hours)-induced mitotic abnormalities, such as formation of elongated spindles, 5,10 and that Plk1 elevation leads to aerobic glycolysis, 13 we then asked whether low-dose arsenic affects the level of Plk1. Toward that end, proteins were prepared from liver, kidney, lung and bladder tissues of mice as described above.…”
Section: Low-dose Arsenic Induces Elevation Of Plk1mentioning
confidence: 99%
See 1 more Smart Citation